Faktor-Faktor Yang Mempengaruhi Konsumen dalam Memilih Sepeda Motor dengan Menggunakan Analisis Faktor (Studi Kasus Mahasiswa Matematika FMIPA UNP) - Resi Arsiva; Arnellis Arnellis (Journal of Mathematics UNP, 2022)
The poor public transportation makes people choose motorbikes as the main transportation. The purpose of this research is to know what factors can influence the consumers in the course of choosing motorbike within study cases on department mathematic of UNP students.The questionnaire distributed  used total sampling technic. There are four factors that influence consumers in the course of choosing motorbike. The first factor is current development, family members, lifestyle, satisfaction to product, learn from experience,  consumer attitude to product, and experience. The second factor is parents profession, economic situation, and parents income. The third factor is friend and  elder people existence. the fourth factor is bad and good viewpoint to product and parents experience.